PENGARUH KECERDASAN SPIRITUAL, KINERJA PELAYANAN PERPAJAKAN, KUALITAS PELAYANAN FISKUS, KETEGASAN SANKSI PERPAJAKAN, PENYELEWENGAN PAJAK, DAN PERSEPSI KEWAJIBAN PAJAK TERHADAP MOTIVASI WAJIB PAJAK DALAM MEMENUHI KEWAJIBAN PERPAJAKAN - Novriandri Putra Ardian; Raja Adri Satriawan Surya; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted at the Tax Office (KPP) Pratama Pekanbaru Tampan. The purpose of this study to examine the influence of spiritual intelligence, taxation service performance, service quality fiksus, firmness tax penalties, tax fraud and tax liabilities perception on the motivation of the individual taxpayer in fulfilling their tax obligations in the Tax Office Primary. To achieve these objectives the research is done by using the sample of 100 respondents, by using the method of data analysis is using Partial Test. Based on the research results of testing the first hypothesis indicates that the variable spiritual intelligence (X1, performance variable tax services (X2, variable quality of service tax authorities (X3) and variable firmness sanction taxes (X4) has an influence on the motivation of the individual taxpayer. While the test results vaiabel hypothesis on tax fraud (X5) and variable perception of tax liability (X6) has no effect on the motivation of the individual taxpayer. Recommendations can be submitted is the next study might consider using a wider research object to the scope of some of the tax office in the city of Pekanbaru.Keywords: The Motivation Of The Individual Taxpayer